The Tree That Grows Crooked: A Reflection on the Self-Determination of the Human Person - López Reyes, Selene Georgina (2025)
This research analyzes the Mexican proverb “A tree that grows crooked never straightens its trunk” from the personalist anthropological perspective of Karol Wojtyla. The objective is to evaluate its validity as a representation of personal experience. Through Wojtyla’s integral experience methodology, whose key stages are induction and reduction, the predestination- like meaning of the proverb is questioned in relation to the concepts of self-determination, self-possession, and self-mastery of the human being. The results reveal that the proverb does not constitute an essential core of meaning regarding the experience of personal freedom and, therefore, self-determination, despite its colloquial use. It is concluded that, although a person is born with certain possibilities and limitations, they retain the capacity for self-determination, freedom, and the ability to achieve fulfillment through fully personal and non-predestined actions.